Brucella secretory protein VceA promotes FOXO1 entry into the nucleus to shift host cell metabolism toward glycolysis - Cao Shuzhu; Han Xinxin; Deng Xingmei; Guo Jia; Liu Liangbo; Zhang Yu; Suleimenov Maratbek; Zhao Tianyi; Li Wei; Ding Jian; Xie Songsong; Zhang Hui (Acta Biochimica et Biophysica Sinica)
Increased glycolytic metabolism is a key step in the reproduction of Brucella and the induction of brucellosis, however, little is known about how this process is regulated during infection. Forkhead box protein O1 (FOXO1) is a transcription factor that regulates energy metabolism. In this study, we employ the yeast two-hybrid system (Y2H) and immunoprecipitation (Co-IP) to reverse screen for the FOXO1 for the first time and identify interactions between FOXO1 and the Brucella secretory protein VceA. Our findings reveal that the Brucella secretory protein VceA colocalizes with FOXO1 in the cytoplasm. Additionally, we observe that infection of macrophages with Brucella abortus 2308 ( S2308) promotes FOXO1 entry into the nucleus, leading to a significant upregulation of glycolysis level in macrophage. Conversely, in a VceA mutant strain (S2308-ΔVceA), we note a significant reduction in the ability of FOXO1 to enter the nucleus, accompanied by a decrease in glycolysis level. Furthermore, Brucella interacts with FOXO1 through the secreted protein VceA, promoting the entry of FOXO1 into the nucleus and thereby altering host metabolic patterns. This study provides insights into the mechanisms by which Brucella invades host macrophages and induces unique metabolic changes. These insights may offer a novel rationale for developing metabolic therapeutic strategies for the treatment and prevention of related diseases.